2005
DOI: 10.1038/sj.onc.1208833
|View full text |Cite
|
Sign up to set email alerts
|

Androgen regulates apoptosis induced by TNFR family ligands via multiple signaling pathways in LNCaP

Abstract: It has been suggested in many studies that combined treatment with chemotherapeutic agents and apoptosisinducing ligands belonging to TNFR family is a more effective strategy for cancer treatment. However, the role of androgen regulation of TNFR family-induced apoptosis in prostate cancer is poorly understood. In this study, we investigated the dose-dependent effects of androgen on TNF-a and TRAIL-mediated apoptosis in LNCaP. To investigate the interaction between the androgen receptor (AR) and the caspase-2 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 36 publications
5
92
0
Order By: Relevance
“…It has also been shown that activated caspase 2 can directly cause the cleavage of BID (Harvey et al, 1997;Droin et al, 2001). In addition, studies have demonstrated that caspase 2, upon different apoptotic stimulations, re-distributes to the nuclei or other subcellular membrane compartments to participate in the execution of the cell death programme (Mancini et al, 2000;Chae et al, 2004;Rokhlin et al, 2005). Our results here demonstrate the interconnection between AR and caspase 2 in the regulation of PL-induced apoptosis in prostate cancer cells.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…It has also been shown that activated caspase 2 can directly cause the cleavage of BID (Harvey et al, 1997;Droin et al, 2001). In addition, studies have demonstrated that caspase 2, upon different apoptotic stimulations, re-distributes to the nuclei or other subcellular membrane compartments to participate in the execution of the cell death programme (Mancini et al, 2000;Chae et al, 2004;Rokhlin et al, 2005). Our results here demonstrate the interconnection between AR and caspase 2 in the regulation of PL-induced apoptosis in prostate cancer cells.…”
Section: Discussionsupporting
confidence: 70%
“…It has been reported that the AR, by repressing the cis-element of the caspase 2 promoter, regulates caspase 2 expression (Rokhlin et al, 2005). Our results presented above indicate the involvement of AR or caspase 2 in PL-induced apoptosis in LNCaP cells.…”
Section: Effect Of Ar or Caspase 2 On Pl-induced Apoptosissupporting
confidence: 77%
“…Together these results imply that MAT inhibits Akt activity and thereby sensitizes LNCaP cells to TRAILinduced apoptosis. In fact, the mechanism underlying LNCaP insensitivity to death receptor stimulation has been shown earlier to involve the PI3K/Akt survival pathway Nesterov et al, 2001;Rokhlin et al, 2002Rokhlin et al, , 2005. The constitutive activation of the PI3K/Akt-pathway observed in many cancer Lignans sensitize prostate cancer cells to TRAIL E Peuhu et al forms can be related, for example, to the loss of PTEN, a lipid phosphatase that negatively regulates the pathway (Vlietstra et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The LNCaP cells have a high constitutive Akt activity, which appears to protect the cells from TRAIL-induced apoptosis Nesterov et al, 2001;Rokhlin et al, 2002Rokhlin et al, , 2005. To analyse the possibility that MAT would sensitize LNCaP cells to TRAIL by inhibiting the PI3K/Akt-pathway, we first analysed whole cell lysates after 1 h of MAT treatment for the levels of phosphorylated Akt (Figure 5a).…”
Section: Mat Sensitizes Lncap Prostate Cancer Cells To Apoptosis Thromentioning
confidence: 99%
“…54 Significantly, AR mutation can directly promote CaP cell growth and suppress the protective role of p53 pointing to tight regulatory loop between AR and p53. 55,56 Ultimately all recurrent disease progresses to a phase in which it is androgen depletion independent. An interesting phenomenon occurs in which antiandrogens begin to act as agonists.…”
Section: Ar and Androgen Depletionindependent Capmentioning
confidence: 99%